Coping, resilience, self-esteem and age as predictors of psychological well-being amongst undergraduate university students - Basson, Monique (University of the Free State, 2021)
Psychological Well-being is considered to be more than merely being free from stress and not having any psychological difficulties. It incorporates positive self-perception, positive relations with others, environmental mastery, autonomy, purpose in life, and emotions focused towards healthy development (Ryff, 1995; Ryff & Singer, 1998; Sosik et al., 2017). Stress is often used in the description of coping, as, without stress, there is no need to cope (Jurji et al., 2018). The coping style that university students adopt is often used as a predictor for PWB and their ease of settling into the university environment (Pluut et al., 2015). Additionally, individuals with high levels of resilience are more often able to maintain PWB in stressful and adverse situations (Shahdadi et al., 2017; Videlock et al., 2016). Moreover, high self-esteem contributes to greater PWB than low self-esteem overall (Swann & Bosson, 2010). PWB is beneficial for adults to live a healthy life, making it an important aspect of one's life in the university years, which can be chaotic and full of psychological stress (Molina-García et al., 2011). This study aimed to investigate which variables or combination of variables (Coping, Resilience, Self-esteem, and Age) explain a significant percentage of the variance in Psychological Well-being (PWB) amongst undergraduate university students. In order to determine the correlations between the variables, a correlational design was central to the non-experimental, quantitative study. This research study made use of an existing set of data from a larger research project. A non-probability convenience sampling method was employed in the original research project to recruit 1191 registered undergraduate university students between the ages of 18 and 29 at the University of the Free State. The sample included participants from all ethnic groups, cultures, languages, genders, provinces, majors and religious backgrounds. The measuring instruments included a biographical questionnaire, Ryff’s Scales of Psychological Well-Being (SPWB), the Resilience Scale (RS), the Coping Strategy Indicator (CSI), and the Rosenberg Self-esteem Scale (RSES). A correlation analyses was conducted, followed by a hierarchical multiple regression analyses which was used to analyse the data. From this, the combination of the predictor variables (Coping, Resilience, Self-esteem, and Age) statistically significantly predicted PWB. In terms of the hierarchical multiple regression results there was one result that was statistically and practically significant. With Self-acceptance as the criterion variable, the hierarchical regression analyses found that the combination of the independent variables (coping, resilience, self-esteem, and age) accounted for 37.3% of the variance in the Self-acceptance scores of the sample indicating a statistically significant result on the 1% level. Practically, this indicates that 37.3% of the variance in the Self-acceptance scores of the university students can be explained by the combination of their coping skills, levels of resilience, their self-esteem, and age. From this, 11.5% of the variance in the Self-acceptance scores of the sample is accounted for by Self-esteem as a statistically significant predictor variable. The medium comparable effect size (f2 = 0.18) suggests that this finding is of practical significance and the statistical significance is at the 1% level. In addition to the hierarchical multiple regression analysis, stepwise regression analyses was further conducted independently for each subscale of the criterion variable (Autonomy, Personal Growth, Positive Relations, Purpose in Life, and Self-acceptance). From the stepwise regression analyses, the discussion of the results focused mainly on self-esteem, which proved to significantly (both practically and statistically) account for the variance in the PWB dimensions. More research on PWB amongst university students in South Africa is required to validate these findings.
Keywords: Dissertation (M.Soc.Sc. (Counselling Psychology))--University of the Free State, 2021; Psychological Well-being; Coping; Resilience; Self-esteem; Age; Undergraduate University Students; Free State; Positive Psychology